Group Counseling with Cognitive Restructuring Technique to Improve The Self-Efficacy and Assertiveness of Students Who Experienced Advanced Study Anxiety - Aliem, Nurul; Sugiharto, Dwi Yuwono Puji; Awalya, Awalya (Jurnal Bimbingan Konseling)
The purpose of this study was to examine the effectiveness of group counseling by using cognitive restructuring technique to improve self-efficacy and assertiveness of Junior High School Mardisiswa 2 Semarang who experienced advanced study anxiety. The quasi-experimental method pre-test – post-test design involving 16 students selected by purposive sampling. The result of data analysis showed that there was an enhancement in self-efficacy and assertiveness after the treatment. The acquisition shows that group counseling by using cognitive restructuring technique is effective to improve self-efficacy and assertiveness of students who experience advanced study anxiety.